Ear type in sheep is associated with the MSRB3 locus. (17th August 2020) - Paris, J. M.; Letko, A.; Häfliger, I. M.; Ammann, P.; Drögemüller, C.
Summary: Ear morphology is an important determinant of sheep breeds. It includes different variable traits such as ear size and erectness, suggesting a polygenic architecture. Here, we performed a comprehensive genome‐wide analysis to identify regions under selection for ear morphology in 515 sheep from 17 breeds fixed for diverse ear phenotypes using 34k SNP genotyping data. GWASs for two ear type traits, size and erectness, revealed a single genome‐wide significant association on ovine chromosome 3. The derived marker alleles were enriched in sheep with large and/or floppy ears. The GWAS signal harboured the MSRB3 gene encoding methionine sulphoxide reductase B3, which has already been found to be associated with different ear types in other species. We attempted whole‐genome resequencing to identify causal variant(s) within a 1 Mb interval around MSRB3 . This experiment excluded major copy number variants in the interval, but failed to identify a compelling candidate causal variant. Fine‐mapping suggested that the causal variant for large floppy ears most likely resides in a 175 kb interval downstream of the MSRB3 coding region.